Economic growth in the post-socialist Russian Federation after 1991: The role of Institutions - Constanze Dobler; Harald Hagemann (Universität Hohenheim, 2011)
The paper emphasizes the transition in Russia and the role institutions played before and during the process. In Russia, a big bang approach was applied. That is to say, transition was conducted all of a sudden, omitting important underlying reforms. This practice should function as a shock therapy. Hence, the approach should leave no other chance than an abrupt adaption to the new free-market rules. These rules would then lead to fast economic growth and development, as they did in other places. However, since Russian GDP per capita and thereby living standards deteriorated dramatically in the years after the collapse of the Soviet Union, the plan did not work. At any rate, since then Russian economic indicators recovered and partly achieved their pre-1991 levels at the end of the last decade. The paper depicts Russia's reform efforts and the subsequent developments. The close ties among the political elite, the banking sector and the old nomenklatura are demonstrated. The patrimonial system that persisted for centuries is still observable at the state level. At any rate, Russia can neither evade its historical and institutional development path nor its societal structures that are based on networks and nepotism. Russia's systemic lack of the rule of law and therewith of secure property, the character of the Russian political system with the patriarch as the head of state and the resulting necessity of corruption and bribes inhibit the realization of its full growth potential.
Keywords: N14; N24; N44; O43; O52; P20; P30; 330; country studies; economic systems; formerly centrally planned economies; growth; institutions; transition economies; Wirtschaftswachstum; Systemtransformation; Schock; Übergangswirtschaft; Institutioneller Wandel; Pfadabhängigkeit; Patronage; Russland